Fig. 1 in Besnoitia tarandi in Canadian woodland caribou - Isolation, characterization and suitability for serological tests - Schares, Gereon; Jutras, Charles; Bärwald, Andrea; Basso, Walter; Maksimov, Aline; Schares, Susann; Tuschy, Mareen; Conraths, Franz J.; Brodeur, Vincent (Zenodo, 2019)
Fig. 1. Besnoitia from Canadian woodland caribou. (A) Besnoitia tarandi tissue cyst in caribou skin (animal H-1145), (B) mechanically released bradyzoites used for mouse or cell culture inoculation and (C) a parasitophorous vacuole in a MARC-145 cell stained by immunofluorescence using a rabbit anti-Besnoitia besnoiti antibody. Published as part of Schares, Gereon, Jutras, Charles, Bärwald, Andrea, Basso, Walter, Maksimov, Aline, Schares, Susann, Tuschy, Mareen, Conraths, Franz J. & Brodeur, Vincent, 2019, Besnoitia tarandi in Canadian woodland caribou - Isolation, characterization and suitability for serological tests, pp. 1-9 in International Journal for Parasitology: Parasites and Wildlife 8 on page 2, DOI:10.1016/j.ijppaw.2018.11.005, http://zenodo.org/record/10668411